Recent Perspectives on the Mechanism of Recurrence After Ablation of Hepatocellular Carcinoma: A Mini-Review - Yang, Jianquan; Guo, Wen; Lu, Man (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. Hepatectomy, liver transplantation and ablation are the three radical treatments for early-stage hepatocellular carcinoma (ESHCC), but not all patients suit for or tolerate surgery, what is more, the donor liver source is limited. Therefore, ablation plays an important role in the treatment of ESHCC. However, some studies have shown that ablation has a higher local recurrence rate than hepatectomy and liver transplantation. The specific mechanism is unknown. The latest perspectives on the mechanism of recurrence after ablation of HCC were described and summarized. In this review, we will discuss the possible mechanisms underlying recurrence after ablation of HCC including epithelial-mesenchymal transition (EMT), activating autophagy, non-coding RNA changing and tumor microenvironment changing. A systematic and comprehensive understanding of the mechanism will contribute to the research and development of related drugs, combined with ablation to improve the therapeutic effect of ESHCC.